2009
DOI: 10.1007/s12011-009-8540-5
|View full text |Cite
|
Sign up to set email alerts
|

Trigonella foenum-graecum (Fenugreek) Protects Against Selenite-Induced Oxidative Stress in Experimental Cataractogenesis

Abstract: Cataract is the opacification in eye lens and leads to 50% of blindness worldwide. The present study was undertaken to evaluate the anticataract potential of Trigonella foenum-graecum Linn seeds (fenugreek) in selenite-induced in vitro and in vivo cataract. In vitro enucleated rat lenses were maintained in organ culture containing Dulbecco's modified Eagles medium (DMEM) alone or in addition with 100 microM selenite and served as the normal and control groups, respectively. For the test group, the medium was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…The seed oil of fenugreek was selected for this study, since fenugreek is commonly used as a spice in food preparations due to the strong flavour and aroma. The seeds are reported to have restorative and nutritive properties (Khosla et al, 1995), such as anti diabetic activity (Sharma et al, 1990), hepatoprotective activity (Thirunavukkarasu et al, 2003;Kaviarasan and Anuradha, 2007), and antioxidant properties against experimental cataract (Gupta et al, 2010). In recent research, fenugreek seeds were experimentally shown to protect against breast (Amin et al, 2005) and colon cancers (Raju et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed oil of fenugreek was selected for this study, since fenugreek is commonly used as a spice in food preparations due to the strong flavour and aroma. The seeds are reported to have restorative and nutritive properties (Khosla et al, 1995), such as anti diabetic activity (Sharma et al, 1990), hepatoprotective activity (Thirunavukkarasu et al, 2003;Kaviarasan and Anuradha, 2007), and antioxidant properties against experimental cataract (Gupta et al, 2010). In recent research, fenugreek seeds were experimentally shown to protect against breast (Amin et al, 2005) and colon cancers (Raju et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Its utility has also been proved experimentally in diabetic humans (Sharma et al, 1990). Hepatoprotective properties of fenugreek seeds in experimental models (Thirunavukkarasu et al, 2003;Kaviarasan and Anuradha, 2007) and antioxidant properties of fenugreek seeds against experimental cataract (Gupta et al, 2010) were also reported. In recent research, fenugreek seeds were experimentally shown to protect against breast (Amin et al, 2005) and colon cancers (Raju et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Several phytoconstituents from herbal origin may indirectly inhibits the consumption of glutathione or it can stimulate the glutathione synthesis which may be due to modulating effect on enzymes that affects glutathione level in lens architecture. In another study, it was found that Trigonella foenum-graceum can enhance the glutathione level due to inhibition of consumption of glutathione (Gupta et al, 2010). Several factors are involved in generation of cataract, but exact mechanism of cataract formation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The extract reduced the enhanced activities of phospholipases A (PLA) and C (PLC) in liver and kidneys and serum marker enzymes: aspartate transaminase (AST), alanine tansaminase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and gamma glutamyl transferase (GGT). It was demonstrated that fenugreek protected against selenite-induced oxidative stress in experimental cataractogenesis in vitro and in vivo [16]. Furthermore, it significantly restored antioxidant enzymes such as SOD, CAT, GPx, and GST and non-enzymatic antioxidant: glutathione and decreased malondialdehyde levels in rats' lenses in culture medium supplemented with selenite together with fenugreek aqueous extract.…”
Section: Trigonella Foenum-graecum L Antioxidant Activitymentioning
confidence: 96%